Landscape characteristics influencing habitat use of grassland birds in the Pampas ecoregion of Argentina - Clara Trofino-Falasco; María G. Pizzarello; María V Simoy; María F. Aranguren; Rosana E. Cepeda; Adrián S Di Giacomo; Claudia B. Marinelli; Gaston Moran; Maria C. Neyra; David G. Vera; Igor Berkunsky (Avian Conservation and Ecology, 2025)
Understanding the influence of landscape composition on grassland bird habitat use is vital for predicting their fate in heavily fragmented ecosystems. During the breeding season, grassland patch metrics and matrix composition are driving factors in grassland bird habitat use. We modeled the use probability of grassland birds based on habitat characteristics during one breeding season in the Tandilia Mountains of Argentina. Between September 2020 and March 2021, we visited 126 field points monthly, recording detected birds within a 100 m radius (sampling unit). For each sampling unit, we calculated (a) the covered area by each land-use type (i.e., groves, crops, pastures, and natural grasslands), (b) the distance to landscape elements (i.e., streams, human settlements, groves, and natural grassland remnants), and (c) the area and shape of the nearest grassland remnant. We analyzed the effect of habitat variables on the use probability for each species through occupancy models. We detected 18 grassland bird species, of which 80% used sites near more circular grassland patches. Sites located on natural grassland remnants showed use probabilities greater than 40%. Other land uses such as perennial pastures, groves, and streams strongly affected the habitat use of grassland birds. Granivores and omnivores used sites with greater perennial pasture coverage, while insectivores and also granivores used sites near groves and away from streams. These results confirm that natural grassland remnants are the main drivers of grassland bird habitat use during the breeding season. Maintaining the integrity of these remnants is essential for grassland bird conservation.